An Introduction To Translation Studies: An Overview - Pradita, Intan (English Education Department, Universitas Islam Indonesia, 2012)
This study aims to observe the development of translation studies through three concepts of descriptive translation studies; product-based, processbased, and functional-based translation studies. The readers are introduced to some famous translation scholars including their view of translation studies. At the further discussions, this study lets the readers acknowledge the main issues on translation studies, focusing on the debate of equivalence versus variations in intertextual texts analysis. Some tendencies of variations, such as different grammar and sentence structure, diglossia leakage, and pragmatic consideration are also presented to present to what extent variations occur during investigation processes. Therefore, regarding those tendencies, this study is closed by the description of Matthiessen's proposals about points of consideration to construct a parameter to measure meaning variations. This study may help those who are interested to conduct translation researches and help them by giving options of which theories is beneficial to their analysis.Key words: translation studies, variations, intertextual texts analysis